Medium-term mortality after hip fractures and COVID-19: A prospective multi-centre UK study - Gareth Chan; Ashish Narang; Arash Aframian; Zaid Ali; Joseph Bridgeman; Alastair Carr; Laura Chapman; Henry Goodier; Catrin Morgan; Chang Park; Sarah Sexton; Kapil Sugand; et al. (Chinese Journal of Traumatology, 2022)
Purpose: The COVID-19 pandemic has caused 1.4 million deaths globally and is associated with a 3–4 times increase in 30-day mortality after a fragility hip fracture with concurrent COVID-19 infection. Typically, death from COVID-19 infection occurs between 15 and 22 days after the onset of symptoms, but this period can extend up to 8 weeks. This study aimed to assess the impact of concurrent COVID-19 infection on 120-day mortality after a fragility hip fracture. Methods: A multi-centre prospective study across 10 hospitals treating 8% of the annual burden of hip fractures in England between 1st March and 30th April, 2020 was performed. Patients whose surgical treatment was payable through the National Health Service Best Practice Tariff mechanism for “fragility hip fractures” were included in the study. Patients’ 120-day mortality was assessed relative to their peri-operative COVID-19 status. Statistical analysis was performed using SPSS version 27. Results: A total of 746 patients were included in this study, of which 87 (11.7%) were COVID-19 positive. Mortality rates at 30- and 120-day were significantly higher for COVID-19 positive patients relative to COVID-19 negative patients (p < 0.001). However, mortality rates between 31 and 120-day were not significantly different (p = 0.107), 16.1% and 9.4% respectively for COVID-19 positive and negative patients, odds ratio 1.855 (95% CI 0.865–3.978). Conclusion: Hip fracture patients with concurrent COVID-19 infection, provided that they are alive at day-31 after injury, have no significant difference in 120-day mortality. Despite the growing awareness and concern of “long-COVID” and its widespread prevalence, this does not appear to increase medium-term mortality rates after a hip fracture.